Solubilized proteins from carrot (Daucus carota L.) membranes bind calcium channel blockers and form calcium-permeable ion channels. - Thuleau, P (1993)
Calcium channels have been suggested to play a major role in the initiation of a large number of signal transduction processes in higher plant cells. However, molecular components of higher plant Ca2+ channels remain unidentified to date. Calcium channel blockers of the phenylalkylamine family and bepridil specifically inhibit Ca2+ influx into carrot (Daucus carota L.) cells. By using a phenylalkylamine azido derivative, a 75-kDa carrot membrane protein has been previously identified. Here we have partially purified this Ca2+ channel blocker-binding protein by lectin-affinity and ion-exchange chromatographies. The protein fraction containing the 75-kDa binding protein was incorporated into giant liposomes. Single-channel patch-clamp studies on these proteoliposomes showed the presence of Ca2+-permeable channel currents. These Ca2+-permeable channels were not stable. Recordings after durations of 2-10 min showed the appearance of nonselective ion channels with a permeability to calcium and chloride ions. These nonselective Ca2+-permeable ion channels, in contrast, were stable and were recorded for extended durations. The addition of the Ca2+ channel-blocker bepridil (10 M) led to the inhibition of these nonselective Ca2+-permeable channels by reducing the probability of channel opening. These results suggest that the 75-kDa Ca2+ channel blocker-binding protein from carrot cells plays a role in channel sensitivity to Ca2+ channel inhibitors and may constitute one of the components of Ca2+ channels in higher plants.